Gymnancyla (Gymnancyla) iranella (Lepidoptera: Pyralidae, Phycitinae),a new species from Iran - Alipanah, Helen; Asselbergs, Jan; Shams-Zadeh, Mehdi (Zootaxa, 2014)
A full description of Gymnancyla (Gymnancyla) iranella sp. n. is given; adult, head and appendages, male and female genitalia and the larva are described and illustrated, based on 15 males, 12 females and three last instar larvae collected in central Iran, Yazd Province, Abarkuh region. Larvae were found on Salsola sp. (family Chenopodiaceae).